Advances in orofacial pain research: a bibliometric analysis - Shuo Qin; Shuo Qin; Juan Liu; JiaXing Fan; Zhe Qin; Jing Jia (Frontiers in Neurology)
ObjectiveOrofacial pain has become increasingly prevalent with the advancement of society and economy. Bibliometrics, an interdisciplinary field encompassing mathematics, statistics, and information science, offers insights into the trends, research focal points, and knowledge framework of orofacial pain through quantitative analysis of relevant literature. This study aims to systematically map the evolutionary trajectory of orofacial pain research from 2000 to 2024. It will analyze publication trends, collaborative networks, and emerging hotspots to provide data-driven guidance for future research directions and resource allocation.MethodsThis study employed bibliometric analysis to examine literature published between 2000 and 2024 using keywords such as “face pain,” “craniofacial pain,” “neuralgic facial pain,” “myofacial pain,” “oral-maxillofacial pain,” “oral and maxillofacial pain,” and “orofacial pain.” Utilizing tools like CiteSpace and VOSviewer, we conducted trend analysis on publication volume, constructed author collaboration networks, and performed keyword co-occurrence analysis.ResultsOur analysis revealed a rising publication trend in the field, the establishment of a core group of authors, continuous expansion of collaboration networks, and current research focal points on “diagnostic criteria,” “manual therapy,” “systematic review,” “quality,” “joint disorders,” “scale,” and “care.”ConclusionThis study demonstrates that bibliometrics offers a comprehensive and objective quantitative analysis for academic research, aiding researchers in understanding disciplinary developments, providing a scientific foundation for future research directions and resource allocation, and fostering sustainable disciplinary growth and innovation.